2024
DOI: 10.1021/acs.macromol.3c02498
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Reactivity of a Novel Methacrylic Transmer in Solution RAFT-SCVP and Its Impact on the Structure of the Resulting Hyperbranched Polymers

Typhaine Despres,
Tiffaine Fabre,
Samuel Legeay
et al.

Abstract: A novel methacrylic-based R-transmer, named 2-(methacryloyloxy)­ethyl 4-cyano-4-(((propylthio)­carbonothioyl)­thio)­pentanoate, was synthesized, and its reactivity (propagation versus reversible chain transfer) in reversible addition–fragmentation chain transfer self-condensing vinyl polymerization (RAFT-SCVP) with methyl methacrylate (MMA) was studied to apprehend its impact on hyperbranched polymers (HBP) structure. The resulting HBP were characterized by nuclear magnetic resonance (NMR) spectroscopy, size e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…This is because the methacryloyl group of CEPEMA can copolymerize with DMAEMA during the RAFT solution polymerization, which undergoes a mixed mechanism of step-growth (condensation of the RAFT group with double bonds) and chain growth (polymerization of double bonds) (Scheme S1). According to work reported by Despres et al, the high-molecular-weight shoulder should be the branched polymer structure with less branching points while the low-molecular-weight peak should be the branched polymer structure with more branching points. As the linear chain length of PDMAEMA n -P­(DMAEMA m - co -CEPEMA)-CEPA ( n + m = 60) increases, the molecular weight distribution of the polymer became narrower due to the decreased fraction of the branched part.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This is because the methacryloyl group of CEPEMA can copolymerize with DMAEMA during the RAFT solution polymerization, which undergoes a mixed mechanism of step-growth (condensation of the RAFT group with double bonds) and chain growth (polymerization of double bonds) (Scheme S1). According to work reported by Despres et al, the high-molecular-weight shoulder should be the branched polymer structure with less branching points while the low-molecular-weight peak should be the branched polymer structure with more branching points. As the linear chain length of PDMAEMA n -P­(DMAEMA m - co -CEPEMA)-CEPA ( n + m = 60) increases, the molecular weight distribution of the polymer became narrower due to the decreased fraction of the branched part.…”
Section: Resultsmentioning
confidence: 94%
“…Figure a shows the 1 H NMR spectra of CEPA, HEMA, and CEPEMA, confirming the successful synthesis of this CTM with high purity. It should be noted that trithiocarbonate-based CTMs with a methacryloyl R-group and a thioalkyl Z-group have rarely been reported. Very recently, Despres et al reported a detailed investigation on solution RAFT-SCVP using a CTM with a similar structure. We then conducted a kinetic study of RAFT solution polymerization of CEPEMA and 2-(dimethylamino)­ethyl methacrylate (DMAEMA) in ethanol with a [CEPEMA]/[DMAEMA] ratio of 1/1 (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…With increasing [CEPEMA]/[HPMA] ratio, the SEC trace shifted to a lower molecular weight. This can be attributed to the increased number of polymers with more branching points as the [CEPEMA]/[HPMA] ratio was increased, leading to the observed decrease in the SEC-characterized molecular weight …”
mentioning
confidence: 99%